Intergenerational transmission of emotion dysregulation: Part II. Developmental origins of newborn neurobehavior. (August 2019) - Ostlund, Brendan D.; Vlisides-Henry, Robert D.; Crowell, Sheila E.; Raby, K. Lee; Terrell, Sarah; Brown, Mindy A.; Tinajero, Ruben; Shakiba, Nila; Monk, Catherine; Shakib, Julie H.; Buchi, Karen F.; Conradt, Elisabeth
Abstract: We investigated whether neurobehavioral markers of risk for emotion dysregulation were evident among newborns, as well as whether the identified markers were associated with prenatal exposure to maternal emotion dysregulation. Pregnant women ( N = 162) reported on their emotion dysregulation prior to a laboratory assessment. The women were then invited to the laboratory to assess baseline respiratory sinus arrhythmia (RSA) and RSA in response to an infant cry. Newborns were assessed after birth via the NICU Network Neurobehavioral Scale. We identified two newborn neurobehavioral factors—arousal and attention—via exploratory factor analysis. Low arousal was characterized by less irritability, excitability, and motor agitation, while low attention was related to a lower threshold for auditory and visual stimulation, less sustained attention, and poorer visual tracking abilities. Pregnant women who reported higher levels of emotion dysregulation had newborns with low arousal levels and less attention. Larger decreases in maternal RSA in response to cry were also related to lower newborn arousal. We provide the first evidence that a woman's emotion dysregulation while pregnant is associated with risks for dysregulation in her newborn. Implications for intergenerational transmission of emotion dysregulation are discussed.